Penguatan Kedudukan Pemasyarakatan dalam Sistem Peradilan Pidana Terpadu melalui Fungsi Pelayanan Tahanan - Riki Afrizal; Iwan Kurniawan; Fajar Wahyudi (Jurnal Ilmiah Kebijakan Hukum, 2023)
Changes in the correctional facility system were marked by the passage of Law Number 22 of 2022 Concerning Correctional Institutions. One of the things that are regulated is regarding detainee services as the correctional function. This arrangement is of course interesting to analyze because so far correctional facilities have only been synonymous with fostering convicts, which is the final stage in the criminal justice system. Services for detainees at the detention center are related to the ongoing criminal justice process because legally the responsibility for detention is still on the law enforcement agencies that carry out the detention. This paper aims to analyze the relationship between the regulation of detainee services in the Correctional Law and the integrated criminal justice system in Indonesia. This study uses a normative juridical method with a statutory and conceptual approach, especially regarding the correctional system and integrated criminal justice system. The results of the discussion and analysis show that there are strict and clear arrangements regarding the administration of detainee services as a function of a correctional facility. This is a form of legal certainty and at the same time affirms the existence of correctional facilities as an integrated criminal justice subsystem. As part of the criminal justice system, correctional facilities do not only work at the end of a series of criminal justice processes through the function of fostering convicts and criminal children but also when the criminal justice process is in operation or progress.